Teaching Speaking Using Identity Cards Through Jigsaw Technique - Ana Safitri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The purpose in this research is to develop the students speaking ability by using identity cards through jigsaw technique. The subject of this study is the students of VII- 2 which consisted of 20 students. The researcher used descriptive qualitative design as the research design. In the finding of the research identity card is a media to teach and make the students interesting and enjoying to learn English. And also, jigsaw technique is a technique to teach and make the students more active to develop their speaking ability. Based on this data, the researcher concludes that using identity cards as materials for teaching speaking through jigsaw technique is a good media and technique to improve the students speaking ability. According to students responses base on chart that can be seen the majority students more interest and enjoy to study, especially using identity cards as materials for teaching speaking through jigsaw technique.